Is Recess an Achievement Context? An Application of Expectancy-Value Theory to Playground Choices - Spencer-Cavaliere, Nancy; Dunn, Janice Causgrove; Watkinson, E. Jane (Alberta Journal of Educational Research, 2009)
This study investigated the application of an expectancy-value model to children’s activity choices on the playground at recess. The purpose was to test the prediction that expectancies for success and subjective task values are related to decisions to engage in specific recess activities such as climbing, playing soccer, or skipping rope. Participants included 242 children in grades 1-4 from five schools. Participation in playground activities was assessed using the Activities for Daily Living in Physical Play (ADL-PP) (Watkinson et al., 2001). Task-specific expectancies and values were measured on the playground activities contained in the ADL-PP. The results indicated that children’s perceptions of competence were significantly higher on playground skills that they had identified as most important compared with least important (p<.001). Multivariate prediction analyses revealed that the data supported the predictions of the model (p<.0001) suggesting that recess can be an achievement context.